Обгрунтування технологічних параметрів отримання гелів на основі полісахаридів різного походження - Бідюк, Дмитро Олегович; Душенок, Дмитро Костянтинович; Перцевой, Федір Всеволодович; Маренкова, Тетяна Іванівна (НТУ "ХПІ", 2018)
В статті наведено дані щодо встановлення впливу різних технологічних факторів – концентрації фурцелларану, напівочищеного каппа-карагенану та камеді конжаку, тривалості та температури гідратації на міцність систем "фурцелларан-камедь конжаку-вода", "напівочищений каппа-карагенан-камедь конжаку-вода". Визначено основні закономірності структуроутворення зазначених систем.

In the article the data on the influence of different technological factors - the concentration of frucellaran, semi-purified kappa-carrageenan and konjac gum, duration and temperature of hydration on the strength of the systems "furcellaran - konjac gum - water", "semi-purified kappa-carrageenan - konjac gum - water" are presented. The purpose of the research is to substantiate the technological parameters of obtaining gel-like structures using furcellaran, semi-purified kappa-carrageenan and konjac gum. The research objectives were to determine the dependencies of the effects of concentrations, the ratio of gelling agents, duration and temperature of dispersion on the strength of the systems under investigation. The conducted studies allowed to determine the dependence of the strength of gels on the basis of furcellaran and konjac gum, as well as semi-purified kappa-carrageenan and konjac gum on the ratio of formulation components. In the course of experimental studies synergic interaction was confirmed in the systems of "semi-purified kappa-carrageenan - konjac gum - water" and "fucellaran - konjac gum - water". It was established that the addition of konjac gum in the ratio of 30%:70% and 40%:60%, according to the composition of gels using semi-purified kappa-carrageenan and fucellaran, results in a significant increase in the strength of the studied systems compared to the control samples.The rational parameters of the hydration of the investigated mixtures are determined. It is reasonable for holding hydration (15...20) ×60s at a temperature no higher than 60°C for mixtures using semi-purified kappa-carrageenan and 40°C - using fucellaran. Determined that the combined use semi-purified kappa-carrageenan and konjac gum, fucellaran and konjac gum is promising and needs further research for the task.
Substantiation of technological parameters of obtaining gels on the basis of polysaccharides of various origins
Keywords: каппа-карагенан; фурцелларан; камедь конжаку; міцність гелю; kappa-сarrageenan; furcellaran; konjac gum